PLURALITY OF TRADITIONS AND UNITY IN ISLAM - Nairthookil, James (Journal of Dharma, 1987)
Every revealed religion maintains a claim to absoluteness which is the result of combining its two attributes, namely, its being universal as well as unique. This assertion of universality and uniqueness makes a revealed religion to evaluate other religions negatively. Hence religious pluralism becomes a threat rather than a positive reality contributing towards a comprehensive vision. If religious pluralism is accepted as a fact there is no difficulty in finding unity in diversity. Islam originated as the latest monotheistic religion in the seventh century. A,D. when Muhammad received the revelation from Allah. Certain tendencies hecame evident in Islam during the course of its growth and development that prevented it from recognizing other religions. Since Muhammad claimed to be "the seal of the prophets," the Muslims considered Islam the final religion which the whole of mankind should embrace. What is implied is that Islam has the monopoly of all the reves lations and guidance necessary for all till the end of the world. Hence the Ahamadiyya sect is considered to be outside the Islamic community because their founder Mirza Ghulam Ahmad claimed to be a propbet many years after the death of Muhammad who was" the seal of the prophets." Though the Qur’anic teaching is that Judaism and Christianity were in essentials the same, Islam has ignored it on the plea that later Jews and Christians have deviated from the original purity of their message. What follows from this is that the salvation of mankind rests on Islam alone. The claim to absoluteness and uniqueness is the natural consequence of this assertion.